Transparent laminated member and face shield using the same

By superimposing a transparent resin base layer and a cured resin layer on the PET board and adding an anti-fog agent, the problems of scratches, whitening, unclear vision and insufficient anti-fog performance during reuse of the mask are solved, and the weather resistance and anti-fog performance of the mask are improved.

JP7671645B2Active Publication Date: 2025-05-02NIPPON PAINT AUTOMOTIVE COATINGS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021120221
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2021-07-21
Publication Date
2025-05-02
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

The PET boards of existing masks are prone to scratches, whitening, and unclear vision when reused, and lack weather resistance to chemicals, and have poor fog resistance, which makes them prone to atomization problems.

Method used

A transparent coating member is used, which is layered from a transparent resin base layer and a transparent curing resin, with a specific light transmission mittance, cloudiness and reflectivity range, and an anti-atomizing agent is added to the transparent curing resin layer to improve anti-atoming performance.

Benefits of technology

The weather resistance and fog resistance of PET sheets are improved, ensuring the transparency and safety of the mask during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671645000022
    Figure 0007671645000022
  • Figure 0007671645000023
    Figure 0007671645000023
  • Figure 0007671645000024
    Figure 0007671645000024
Patent Text Reader

Abstract

To provide a transparent laminated member that allows a face shield to have durability, chemical resistance and anti-fogging properties, wherein the transparent laminated member can be provided with an antireflection layer and allows for the long-term use of the face shield.SOLUTION: A transparent laminated member has a transparent resin substrate layer and a transparent curable resin layer in a laminated manner. The transparent laminated member has a total light transmittance, turbidity, contact angle and reflectance to be controlled within predetermined ranges, so that the transparent laminated member exhibits excellent performances.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent laminated member and a face shield using the same. [Background technology]

[0002] The novel coronavirus infection, known as COVID-19, has spread globally, infecting many people. In addition to masks, face shields have been attracting attention as a way to avoid infection. As shown in Figure 1, a face shield is made by attaching a sponge to the edge of a transparent plastic plate, and a band is used to hold the sponge part against the head. PET plates are usually used for the transparent plastic plate.

[0003] Currently, face shields are inexpensive and can be disposed of after one day of use, but discarding plastic is not good for the environment, so there is a demand for reuse. However, PET sheets alone can become scratched and white when wiped for repeated use, making them less visible. In addition, strict chemical resistance is required because they can be wiped with chemicals such as alcohol or sodium hypochlorite, or touched when putting on or taking off with hands that have touched these chemicals. Furthermore, face shields are required to be anti-fogging so that they do not fog up due to exhaled air.

[0004] In order to achieve long-term use of face shields, a film called a hard coat is formed on a PET sheet, and anti-fogging properties can be imparted to the hard coat layer by adding a surfactant to the hard coat. However, the surfactant molecules are smaller than the matrix network of the hard coat layer, and the surfactant bleeds out or precipitates on the surface, a phenomenon called blooming. Therefore, a PET sheet having a hard coat with anti-fogging properties that does not cause surfactant bleed-out or blooming is desired. In addition, if the hard coat layer itself has a certain degree of hydrophilicity, fogging is less likely to occur.

[0005] Japanese Patent No. 5985100 (Patent Document 1) describes a transparent laminate with low reflection and excellent transparency, visibility, anti-fogging properties, and wipeability, but the low reflectivity is achieved by the unevenness formed on the surface. However, the unevenness on the surface is fragile and scratches are generated by disinfection or rubbing with alcohol.

[0006] JP 2010-106282 A (Patent Document 2) discloses a coating composition having anti-reflection and anti-fogging properties, which is composed of an inorganic metal oxide and a siloxane polymer. This coating also does not have sufficient durability against rubbing with alcohol or disinfectants. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 5985100 [Patent Document 2] JP 2010-106282 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention provides a transparent layer member that can impart durability, chemical resistance, and anti-fogging properties to a PET plate used in a face shield. The transparent laminate member of the present invention can also be provided with an anti-reflection layer, enabling the face shield to be used for a long period of time. [Means for solving the problem]

[0009] That is, the present invention provides the following aspects: [1] A transparent laminated member having a transparent resin substrate layer and a transparent cured resin layer laminated thereon, When the total light transmittance of the transparent laminated member is Tt1, the turbidity is Hz1, and the reflectance is R1, 90% <Tt1<98%、 0.01%≦Hz1<2.0%, and 0.5%≦R1<5.0% Satisfy the relationship between The present invention is characterized in that, when distilled water is poured into a glass container having an opening of 5 cm in diameter so that the height of the container surface from the water surface is 5 cm, the temperature is kept at 60°C, and the glass container is covered with a lid so that the cured resin layer side of the transparent laminate member is in contact with water vapor, no fogging occurs for 3 seconds; The transparent cured resin layer was wiped 100 times with cotton soaked in 6% hypochlorous acid solution under a load of 50 g per unit area. After this, the total light transmittance of the transparent laminated member was Tt2, the turbidity was Hz2, and the reflectance was R2. 0≦|Tt1-Tt2|<1, 0≦|Hz1-Hz2|<2, and 0≦|R1-R2|<0.5 A transparent laminate member according to claim 1, wherein when distilled water is poured into a glass container having an opening of 5 cm in diameter so that the height of the container surface from the water surface is 5 cm, the temperature is kept at 60°C, and the glass container is covered with a lid so that the cured resin layer side of the transparent laminate member is exposed to water vapor, no fogging occurs for 3 seconds. [2] Ibid. 6% hypochlorous acid solution The transparent laminated material of [1] above, which shows the same relationship between total light transmittance, turbidity and reflectance even when replaced with a 3% hydrogen peroxide solution, a 70% ethanol solution or an isopropyl alcohol solution. [3] The transparent cured resin layer comprises two layers, The first layer laminated on the transparent resin substrate layer has a thickness of 2 to 10 μm and a refractive index of 1.48 〜1.54, The transparent laminate member according to [1] or [2], wherein the second layer laminated on the first layer has a thickness of 70 to 130 nm and a refractive index of 1.36 to 1.42. [4] The transparent laminate member according to any one of [1] to [3], wherein the transparent resin substrate is made of a polyester resin and has a thickness of 75 to 250 μm. [5] The transparent cured resin layer has a chemical formula: [ka] (In the chemical formula, n, m, and o each independently represent an integer, and n+m+o=12 to 24.) The transparent laminate member according to any one of [1] to [4], comprising an acrylic-modified isocyanurate (I) having the following formula: [6] The transparent laminate member according to [5], wherein the acrylic-modified isocyanurate (I) is contained in a resin forming the transparent cured resin layer in an amount of 65 to 95% by weight of the resin solid content. [7] The transparent laminate member according to [5] or [6] above, wherein the cured resin layer contains an unsaturated compound (II) having either a hydroxyl group or an unsaturated double bond group and a difunctional or higher unsaturated double bond group in an amount of 5 to 35% by weight based on the weight of the resin component; and The unsaturated compound (II) has the following chemical formula: [ka] [ka] [ka] (In the chemical formula, R, R 1 and R 2 each independently represents a hydroxyl group or -OCO-CH=CH2.) A transparent laminate member comprising any one of the following: [8] The transparent laminate member according to any one of [1] to [7] above, characterized in that the cured resin layer constituting the second layer contains hollow silica having an average particle size of 35 to 70 nm in an amount of 35 to 65% by solid content. [9] A face shield using the transparent laminate member according to any one of [1] to [8] above. Effect of the Invention

[0010] In the present invention, the transparent laminate member is composed of a transparent resin substrate and a transparent cured resin layer laminated thereon, and when the total light transmittance, turbidity, and reflectance of the transparent laminate member are measured, the numerical ranges that each of them satisfies are specified, and the transparent cured resin layer is wiped with cotton soaked in a 6% hypochlorous acid solution, a 3% hydrogen peroxide aqueous solution, a 70% ethanol solution, and a 70% IPA solution, and the difference between the total light transmittance, turbidity, and reflectance of the transparent laminate member is within a specific range. When the transparent laminate member has properties within the above-mentioned specified ranges, the transparent laminate member has transparency, durability, and chemical resistance that can be used for a face shield. Moreover, when the transparent cured resin layer contains a surfactant that imparts anti-fogging properties (hereinafter referred to as "anti-fogging agent"), the transparent laminate member laminated thereon has anti-fogging properties. When this transparent laminate member is used for a face shield, a member that satisfies durability, chemical resistance, and anti-fogging properties can be obtained.

[0011] In order to provide the transparent cured resin layer with an anti-reflection function, the layer may have a two-layer structure, with the layer in contact with the transparent resin substrate as the first layer and the layer not in contact with the transparent resin substrate as the second layer, and the phase difference between light reflected on the surface of the second layer and light passing through the second layer and reflected on the surface of the first layer may be reversed to cancel each other out, thereby providing an anti-reflection function.

[0012] The transparent cured resin layer (or anti-reflection layer) of the present invention, when formed from a crosslinked polymer of isocyanurate of an acrylic-modified aliphatic diisocyanate, has a polyethylene glycol chain in itself, and is therefore hydrophilic, and therefore has a function of being less likely to cause fogging. In addition, the transparent cured resin layer of the present invention has a high ability to retain the anti-fogging agent in the matrix of the transparent cured resin layer (or anti-reflection layer), and a transparent laminate member that exhibits a long-term anti-fogging effect without bleeding out or blooming and has high durability can be obtained. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic perspective view of a face shield. [Diagram 2]FIG. 2 is a schematic cross-sectional view of the transparent laminate member of the present invention having a two-layer structure. [Diagram 3] FIG. 2 is a schematic cross-sectional view of the transparent laminate member of the present invention having a three-layer structure. [Figure 4] FIG. 1 is a diagram showing a five-level evaluation standard for scratch resistance in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The transparent laminate member A of the present invention is of two types, one consisting of two layers, a transparent resin substrate layer 1 and a transparent cured resin layer 2 formed thereon, as shown in Fig. 2, and the other consisting of an antireflection layer 3 further formed on the transparent cured resin layer 2, as shown in Fig. 3. The antireflection layer 3 is a layer that is provided as necessary, but when used for a face shield, for example, it is preferable to provide the antireflection layer 3 because a reflected image can cause misalignment of the hand when working with the hands.

[0015] In this specification, when a numerical range is expressed as "a to b," it means "a or more and b or less," unless otherwise specified. Of course, as will be described later, when a numerical range is expressed with ≦ or <, it is treated as the notation generally used in mathematics.

[0016] In the transparent laminate member A of the present invention, when the total light transmittance of the transparent laminate member A is Tt1, the turbidity is Hz1, and the reflectance is R1, 90% <Tt1<98%、 0.01%≦Hz1<2.0%, and 0.5%≦R1<5.0% Satisfy the relationship between The transparent cured resin layer 2 is wiped 100 times with cotton soaked in 6% sodium hypochlorite solution under a load of 50 g per unit area. After this, the total light transmittance of the transparent laminated member A is Tt2, the turbidity is Hz2, and the reflectance is R2. 0≦|Tt1-Tt2|<2, 0≦|Hz1-Hz2|<2, and 0≦|R1-R2|<0.5 It is necessary to satisfy the relationship:

[0017] In this specification, "total light transmittance" is the percentage of light transmitted, and "turbidity" is an index showing the degree of haze. For the measurement, NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd. is used, and the light source and method are set to D65 and JIS, and the coating surface is placed on the light receiver side to measure the total light transmittance and parallel light transmittance. Here, diffuse light transmittance = total light transmittance - parallel light transmittance Turbidity (Hz) is calculated as: diffuse light transmittance / total light transmittance.

[0018] In this specification, the term "reflectance" refers to the ratio of the reflected light flux from the coating film to the solar radiation incident on the coating film surface, calculated from the spectral reflectance obtained in a specified wavelength range. The reflectance is obtained in the entire wavelength range (wavelength: 380 nm to 780 nm) according to JIS K 5602. Specifically, the reflectance is measured using SD7000 manufactured by Nippon Denshoku Industries Co., Ltd. under the conditions shown in the examples.

[0019] In the present invention, when the total light transmittance is expressed as Tt1%, the turbidity is expressed as Hz1%, and the reflectance is expressed as R1%, the values ​​are 90% <Tt1<98%、 0.01%≦Hz1<2.0%, and 0.5%≦R1<5.0% The relationship above must be satisfied. The higher the total light transmittance, the better the transparency, so a value exceeding 90% is necessary, while the closer to 100%, the better the characteristics, but even if an anti-reflection design is adopted, a design exceeding 98% is not realistic. The lower the turbidity Hz1, the higher the transparency, so it must be 0.01% or more and less than 2.0%, preferably 0.01 to 1.50%, and more preferably 0.01 to 1.00%. The reflectance R1 is preferably not high, and must be 0.5% or more and less than 5.0%, but is preferably 0.5 to 3.5%, and more preferably 0.5 to 2.5%.

[0020] The transparent laminate member A of the present invention further has a total light transmittance of Tt2, a turbidity of Hz2, a contact angle of C2, and a reflectance of R2 after a wiping test in which the transparent cured resin layer 2 is wiped 100 times with cotton soaked in 6% hypochlorous acid solution under a load of 50 g per unit area, where the total light transmittance of the transparent laminate member A is Tt2, the turbidity is Hz2, the contact angle is C2, and the reflectance is R2. 0%≦|Tt1-Tt2|<1%, 0%≦|Hz1-Hz2|<2%, and 0%≦|R1-R2|<0.5% It is necessary to satisfy the relationship of. This test is a test for measuring chemical resistance, and can be measured using various chemicals, and a chemical with high usability is selected for testing, but in the present invention, it was determined that sodium hypochlorite is suitable for use as a face shield. A 6% sodium hypochlorite solution is soaked into cotton, and a wiping test is performed 100 times under a load condition of 50 g per unit area to evaluate. When the total light transmittance of the transparent laminated member A after this wiping test with sodium hypochlorite is Tt2, the turbidity is Hz2, and the reflectance is R2, the absolute value of the difference from the value before the wiping test is calculated, and if the value is within the above range, it is determined that the durability and chemical resistance are high.

[0021] The absolute value of the difference between the values ​​of total light transmittance Tt before and after the wipe test is preferably small, and is higher than 0% and less than 1%, preferably 0 to 0.6%, and more preferably 0 to 0.3%. The absolute value of the difference between the values ​​of turbidity Hz before and after the wipe test is preferably small, and is higher than 0% and less than 2%, preferably 0 to 0.8%, and more preferably 0 to 0.3%. The absolute value of the difference between the values ​​of reflectance R before and after the wipe test is preferably small, and is higher than 0% and less than 0.5%, preferably 0 to 0.4%, and more preferably 0 to 0.3%.

[0022] The transparent laminate member A of the present invention also requires anti-fogging properties. Anti-fogging properties are measured by pouring distilled water into a glass container with an opening of 5 cm in diameter so that the height of the container surface from the water surface is 5 cm, keeping the temperature at 60°C, and covering the glass container with a lid so that the transparent cured resin layer 2 side of the transparent laminate member A is in contact with water vapor. The transparent laminate member A of the present invention requires that no fogging occurs for 3 seconds under these conditions. The longer the anti-fogging time, the better, but if no fogging occurs for 3 seconds, it is usually judged to have high rust prevention properties.

[0023] In the present invention, it is preferable that the high rust prevention properties described above are maintained even after the above-mentioned wipe test using a 6% hypochlorous acid solution.

[0024] In the present invention, the wipe test using the 6% hypochlorous acid solution may be replaced with a 70% isopropyl alcohol solution, a 3% aqueous hydrogen peroxide solution, or a 70% ethanol solution, and the test using these solutions must also show the relationship between the total light transmittance, turbidity, and reflectance within the same range as above. Here, the "solution" refers to an aqueous solution, and for example, a 3% aqueous hydrogen peroxide solution is an aqueous solution containing 3% by weight of hydrogen peroxide water.

[0025] In the present invention, as shown in FIG. 3, an antireflection layer 3 may be provided on the transparent cured resin layer 2. The antireflection layer 3 has a layer (transparent cured resin layer 2) that is in contact with the transparent resin substrate 1 as the first layer and a layer (antireflection layer 3) that is not in contact with the transparent resin substrate 1 as the second layer, and the phase difference between the light reflected on the surface of the second layer and the light that passes through the second layer and is reflected on the surface of the first layer is reversed to cancel each other out, thereby preventing reflection. In short, the antireflection function depends on the thickness and refractive index of the transparent cured resin layer 2 (first layer) and the thickness and refractive index of the antireflection layer 3 (second layer). In the present invention, it is required that the first layer has a thickness of 2 to 10 μm and a refractive index of 1.48 to 1.54, and the second layer laminated on the first layer has a thickness of 70 to 130 nm and a refractive index of 1.36 to 1.42.

[0026] As described above, the anti-reflection layer 3 is determined by its thickness and refractive index, and the refractive index is determined by the resin used. In order to change the refractive index, a material that changes the refractive index is added without affecting the transparency of the resin layer. In a preferred embodiment of the present invention, the transparent cured resin layer 2 and the anti-reflection layer 3 are formed of the same material described below, and therefore, it is common to blend highly transparent inorganic particles, such as hollow silica particles having an average particle size of 35 to 70 nm, in the anti-reflection layer 3 to change the refractive index. In the present invention, it is preferred that hollow silica particles having an average particle size of 35 to 70 nm are blended in the anti-reflection layer 3 in an amount of 35 to 65% by weight of solid content.

[0027] The transparent laminated member of the present invention, as shown in FIG. 2 and FIG. 3, is composed of a transparent resin substrate 1, a transparent cured resin layer 2, and an anti-reflection layer 3 as required. The transparent resin substrate 1 is generally made of a polyester resin, particularly a so-called PET resin (polyethylene terephthalate resin). Resins other than polyester resins, such as polyolefin resins (e.g., polyethylene resins and polypropylene resins), polyamide resins, etc., may also be used, but polyester resins, particularly PET resins, are preferably used in consideration of transparency and versatility. The transparent resin substrate 1 has a thickness of 75 to 250 μm, preferably 75 to 188 μm, and more preferably 100 to 125 μm. It may be thicker than 250 μm, but if it is too thick, it will not be possible to bend it when used in a face shield that is bent to some extent. Conversely, if the thickness is too thin, the strength will be insufficient.

[0028] The transparent cured resin layer 2 and the antireflection layer 3 of the present invention are preferably made of the same material, and a resin used in a so-called hard coat can be used, but since an antifogging agent is contained in the resin layer to impart antifogging properties, it is preferable to use a polymer material that does not cause bleed-out or blooming, and in the present invention, an isocyanurate of an acrylic-modified aliphatic diisocyanate is used as a monomer to obtain the transparent cured resin layer 2 or the antireflection layer 3. Hereinafter, the term transparent cured resin layer includes the case where the antireflection layer is formed from the same material.

[0029] The chemical formula of the acrylic modified aliphatic diisocyanate isocyanurate can be represented as follows: [ka] (In the chemical formula, n, m, and o each independently represent an integer, and n+m+o=12 to 24.)

[0030] This monomer is formed by reacting one of the isocyanate groups of hexamethylene diisocyanate with ethylene glycol, further capping the end having a hydroxyl group with acrylic acid, and converting the remaining isocyanate group into an isocyanurate. When this monomer is applied to the transparent resin substrate together with a polymerization initiator, particularly a photopolymerization initiator, used in the polymerization of ordinary unsaturated double bonds and cured, a three-dimensionally crosslinked transparent film, particularly a hard coat layer, is formed. This transparent cured resin layer is capable of holding the antifogging agent described later in the polymer matrix, and is excellent for forming an antifogging material.

[0031] In the above chemical formula of the acrylic modified isocyanurate (I), n, m, or o means the number of ethylene glycols added, and n+m+o represents an integer of 12 to 24. n+m+o is preferably 16 to 24, and more preferably 18 to 24. If the number of ethylene glycols added is less than 12, it becomes difficult to achieve high antifogging properties.

[0032] The acrylic modified isocyanurate (I) used in the present invention can be produced by reacting an isocyanurate trimer of hexamethylene diisocyanate with polyethylene glycol mono(meth)acrylate. Polyethylene glycol mono(meth)acrylates exist with various molecular weights depending on the number of polyethylene glycol bonds, and various products are commercially available from NOF Corporation under the trademark BLEMMER, so the total number of n, m, and o (n+m+o) of the acrylic modified isocyanurate (I) can be adjusted depending on the type of polyethylene glycol mono(meth)acrylate used.

[0033] The transparent cured resin layer of the present invention may be formed by curing only the acrylic modified isocyanurate (I) as a constituent to form a resin component, but it is generally preferred that an unsaturated compound (II) having either a hydroxyl group or an unsaturated double bond group and an unsaturated double bond group having two or more functionalities is contained in an amount of 0 to 35% by weight based on the weight of the resin component. This unsaturated compound (II) can be a compound having one hydroxyl group and two or more unsaturated double bond groups, or a compound having three or more unsaturated double bond groups when all of the unsaturated double bond groups are unsaturated double bond groups. A small amount of hydroxyl groups is necessary for the purpose of maintaining hydrophilicity, and unsaturated double bond groups are necessary for crosslinking, and a compound having both groups or a compound having three or more functionalities when only unsaturated double bond groups are used. The amount used is 0 to 35% by weight based on the weight of the resin component, but is preferably 5 to 25% by weight, and more preferably 5 to 20% by weight.

[0034] <Unsaturated compound (II)> The unsaturated compound (II) has either a hydroxyl group or an unsaturated double bond group, and an unsaturated double bond group with two or more functionalities. Specifically, the unsaturated compound (II) has the following chemical formula: [ka] [ka] [ka] (In the chemical formula, R, R 1 and R 2 each independently represents a hydroxyl group or -OCO-CH=CH2.) The monomer compounds (II-a) to (II-c) have the following formula:

[0035] This monomer compound (II-a) is an isocyanurate of ethylene diisocyanate, in which one end of ethylene diisocyanate is completely blocked with acrylic acid, or one of the three OH groups is left as it is. Such monomer compounds (II-a) are commercially available and exist as a mixture of those in which R is a hydroxyl group and those in which R is an acrylic end. When the monomer compound (II-a) is used as this mixture, the obtained transparent cured resin layer has appropriate hydrophilicity, durability, chemical resistance, antifogging properties, and antireflection properties. In the present invention, it is believed that a compound having an isocyanurate ring, such as the monomer compound (II-a), is necessary for performance such as durability. Therefore, as the unsaturated compound (II) having either one of a hydroxyl group or an unsaturated double bond group and an unsaturated double bond group having two or more functionalities, the above-mentioned monomer compound (II-a) is currently the most suitable.

[0036] The above monomer compounds (II-b) and (II-c) are also monomers corresponding to the unsaturated compound (II) and are particularly useful. These are polyhydric alcohol compounds in which all alcohol ends are capped with acrylic acid or one hydroxyl group is left. 1 Or R 2 represents either a hydroxyl group or -OCO-CH=CH2. Both monomer compounds (II-b) and (II-c) are commercially available. 1 Or R 2 Mixtures of those in which R is a hydroxyl group and those in which R is an acryl terminal group are present. These can also be used effectively.

[0037] As described above, the monomer compounds (II-a) to (II-c) used as the unsaturated compound (II) are usually provided as a mixture of two types of monomers, and the monomer species is R(R 1 and R 2 The monomer compounds (II) include those in which R is a hydroxyl group and those in which R is an acrylic terminal, and the ratio of those in which R is a hydroxyl group is 1 to 50% by weight, preferably 3 to 40% by weight, of the total amount of the monomer compounds (II). Those in which R is a hydroxyl group are not necessary, but hydrophilicity tends to be insufficient.

[0038] When forming a transparent cured resin layer, it is preferable that the acrylic modified isocyanurate (I) is contained in an amount of 65 to 100% by weight based on the solid weight of the total monomer, and the unsaturated compound (II) is contained in an amount of 0 to 35% by weight based on the weight of the resin component in the composition. Preferably, the acrylic modified isocyanurate (I) is 75 to 95% by weight, more preferably 80 to 95% by weight based on the weight of the resin component. The unsaturated compound (II) is blended in an amount obtained by excluding the acrylic modified isocyanurate (I) from 100% by weight. If the acrylic modified isocyanurate (I) is less than 65% by weight based on the weight of the resin component, the antifogging property is insufficient when a cured film is formed. Although the acrylic modified isocyanurate (I) can be used at 100% by weight based on the weight of the resin component, when better performance such as chemical resistance is to be obtained, it is better to control the performance by including the unsaturated compound (II).

[0039] <Photopolymerization initiator> The combination of the acrylic modified isocyanurate (I) and, if necessary, the unsaturated compound (II) is made UV-curable by combining it with a photopolymerization initiator. The photopolymerization initiator may be any one capable of generating radicals as active species upon irradiation with light, and any known radical photopolymerization initiator may be used without any limitations. Specific examples include acetophenones such as diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one; 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime )], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(0-acetyloxime) and other oxime esters; benzoins such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone, o-benzoylbenzoic acid methyl ester, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, and (4-benzoylbenzyl)trimethylammonium chloride;Thioxanthones such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; and acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, triethanolamine, triisopropanolamine, 4,4'-dimethylaminobenzophenone (Michler's ketone), 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, 4-dimethylaminobenzoic acid ethyl, 4-dimethylaminobenzoic acid (n-butoxy)ethyl, 4-dimethylaminobenzoic acid isoamyl, 4-dimethylaminobenzoic acid 2-ethylhexyl, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, etc. may be used in combination as an auxiliary for the photopolymerization initiator. The above photopolymerization initiators and auxiliary agents can be synthesized by known methods and are also available as commercial products.

[0040] The content of the photopolymerization initiator is not particularly limited, and may be appropriately adjusted within a range in which the polymerization reaction (radical polymerization) of the radical polymerizable compound proceeds well. For example, the content is in the range of 0.1 to 20 parts by weight, preferably 0.5 to 10 parts by weight, more preferably 1 to 10 parts by weight, based on 100 parts by weight of the polymerizable compound (the combination of the acrylic modified isocyanurate (I) and, if necessary, the unsaturated compound (II)) contained in the composition.

[0041] The combination of the acrylic modified isocyanurate (I) and, if necessary, the unsaturated compound (II) is applied to a substrate together with a solvent, and when irradiated with ultraviolet light, it is cured by ultraviolet light to form a transparent cured resin layer. The thickness is not particularly limited, but can be changed depending on the intended use, and in the case of a transparent cured resin layer, the thickness is 2 to 10 μm, preferably 4 to 8 μm, and when used as an anti-reflection layer, the thickness is 70 to 130 nm, preferably 80 to 120 nm.

[0042] <Other> The transparent cured resin layer of the present invention may contain an antifogging agent (a surfactant that imparts antifogging properties). When the transparent cured resin layer contains an antifogging agent, the transparent cured resin layer has high antifogging properties. The antifogging agent is usually smaller in molecular weight than the polymer matrix of the transparent cured resin layer, and is prone to the phenomenon of bleed-out and blooming. When the above-mentioned acrylic modified isocyanurate (I) is used, even if the antifogging agent bleeds out or blooms, the base matrix itself has antifogging properties, and the antifogging properties are not lost even after long-term use.

[0043] As the anti-fogging agent, anionic, cationic, nonionic, or amphoteric surfactants can be used, for example, sorbitan-based surfactants such as sorbitan monostearate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monobehenate, and esters of condensates of sorbitan and alkylene glycol with fatty acids; glycerin-based surfactants such as glycerin monopalmitate, glycerin monostearate, glycerin monolaurate, diglycerin monopalmitate, glycerin dipalmitate, glycerin distearate, diglycerin monopalmitate / monostearate, triglycerin monostearate, triglycerin distearate, or alkylene oxide adducts thereof; polyethylene glycol monostearate, polyethylene glycol monopalmitate, polyethylene glycol a Examples of the surfactant include polyethylene glycol surfactants such as alkylphenyl ether; trimethylolpropane surfactants such as trimethylolpropane monostearate; pentaerythritol surfactants such as pentaerythritol monopalmitate and pentaerythritol monostearate; alkylene oxide adducts of alkylphenols; esters of sorbitan / glycerin condensates and fatty acids, esters of sorbitan / alkylene glycol condensates and fatty acids; sodium diglycerol diolate lauryl sulfate, sodium dodecylbenzenesulfonate, cetyltrimethylammonium chloride, dodecylamine hydrochloride, lauric acid laurylamide ethyl phosphate, triethylcetylammonium iodide, oleylaminodiethylamine hydrochloride, dodecylpyridinium salts, and isomers thereof. The antifogging agent may have a functional group that reacts with a curable monomer or oligomer.

[0044] The amount of the anti-fogging agent added may be, for example, in the range of 0.01 to 20 parts by weight (in some embodiments, 0.1 to 15 parts by weight, or 0.2 to 10 parts by weight) per 100 parts by weight in total of the photopolymerization initiator and the curable monomer (the combination of the acrylic-modified isocyanurate (I) and, if necessary, the unsaturated compound (II)).

[0045] The transparent cured resin layer of the present invention may contain additives to complement the coating workability. In the present invention, since the layer exhibits not only hydrophilicity but also water absorption, the anti-fogging properties are not impaired even if a silicon-based surface conditioner is contained. However, in consideration of bleed-out, it is preferable to select a surface conditioner containing an unsaturated double bond, and the amount of the surface conditioner to be added is preferably small. Specifically, by adding 0.01 to 0.03 parts by weight of BYK-UV3570 in terms of the resin solid content ratio, it is possible to obtain a cured film that does not affect the anti-fogging properties or durability while greatly improving the coating workability.

[0046] As described above, the anti-reflection layer (second layer) 3 of the present invention is required to have a thickness of 70 to 130 nm and a refractive index of 1.36 to 1.42. The anti-reflection layer 3 is formed of the same material as the transparent cured resin layer 2, and contains an anti-fogging agent to impart anti-fogging properties. In this case, the film thickness can be changed during coating, but as already described, the refractive index is generally adjusted by blending highly transparent inorganic particles, such as hollow silica particles having an average particle diameter of 35 to 70 nm. The average particle diameter of the hollow silica particles is preferably smaller than the film thickness to be formed, and more preferably 75% or less of the film thickness to be formed. The amount of the compound added to the anti-reflection layer 3 is such that the refractive index decreases and the anti-reflection properties are improved as the amount added increases, but a filling amount of 70% or more is not preferable because it impairs the resin properties.

[0047] The transparent laminated member of the present invention may have a two-layer structure as shown in Fig. 2 or a three-layer structure as shown in Fig. 3, but when the transparent laminated member of the present invention is used as the face shield of Fig. 1, an embodiment in which an anti-reflection layer 3 is provided on the transparent cured resin layer 2 as shown in Fig. 3 is preferable. If the face shield is formed in this embodiment, it can be used repeatedly for a long period of time, and in that case, it can be used repeatedly by soaking a cloth in a solvent or chemical and wiping it off, or by removing viruses (sterilizing) with a 6% hypochlorous acid solution or a 3% hydrogen peroxide aqueous solution, and it has a function of maintaining anti-fogging properties for a long period of time, which greatly improves the disadvantages of face shields that are currently discarded after one use. In addition, the anti-reflection layer 3 also has high durability and chemical resistance, so it can be used as a face shield that maintains its anti-reflection function for a long period of time and is easy to handle manually. EXAMPLES

[0048] The present invention will be described in more detail with reference to examples, but it should not be construed that the present invention is limited to these examples.

[0049] Synthesis Example 1 (24 moles of ethylene glycol unit: using Blenmar PE350) The following three raw materials are placed in a 3 L separable flask equipped with a stirrer and an air inlet tube. Isocyanate compound mainly composed of nurate type trimer of hexamethylene diisocyanate (Duranate TPA-100, manufactured by Asahi Kasei Chemicals Corporation, NCO content 23%) 1369.5g (NCO 7.5 mol) 2,6-di-tert-butyl-4-methylphenol (hereinafter referred to as "BHT") 2.30g Dibutyltin dilaurate (hereinafter referred to as "DBTL") 1.35g While stirring at a liquid temperature of 50 to 70° C., 3180 g (7.5 mol) of Blenmer PE-350 was added dropwise. After the dropwise addition was completed, the mixture was stirred at 80° C. for 4 hours, and the reaction was terminated when it was confirmed by IR (infrared absorption) analysis of the reaction product that the isocyanate group had disappeared, thereby obtaining an isocyanuric ring-containing urethane (meth)acrylate compound (corresponding to the acrylic modified isocyanurate (I) of the present invention).

[0050] Synthesis Example 2 (13 to 14 moles of ethylene glycol unit: using Blenmer PE200) The following three raw materials are placed in a 3 L separable flask equipped with a stirrer and an air inlet tube. Isocyanate compound mainly composed of nurate type trimer of hexamethylene diisocyanate (Duranate TPA-100, manufactured by Asahi Kasei Chemicals Corporation, NCO content 23%) 1369.5g (NCO 7.5 mol) BHT 1.70g DBTL 1.03g While stirring at a liquid temperature of 50 to 70° C., 2025 g (7.5 mol) of Blenmer PE-200 was added dropwise. After the dropwise addition was completed, the mixture was stirred at 80° C. for 4 hours, and the reaction was terminated when it was confirmed by IR (infrared absorption) analysis of the reaction product that the isocyanate group had disappeared, thereby obtaining an isocyanuric ring-containing urethane (meth)acrylate compound (corresponding to the acrylic modified isocyanurate (I) of the present invention).

[0051] Synthesis Example 3 (6 moles of ethylene glycol unit: Blenmer PE90 used) The following three raw materials are placed in a 3 L separable flask equipped with a stirrer and an air inlet tube. Isocyanate compound mainly composed of nurate type trimer of hexamethylene diisocyanate (Duranate TPA-100, manufactured by Asahi Kasei Chemicals Corporation, NCO content 23%) 1369.5g (NCO 7.5 mol) BHT 1.30g DBTL 0.81g While stirring at a liquid temperature of 50 to 70° C., 1200 g (7.5 mol) of Blenmer PE-90 was added dropwise. After the dropwise addition was completed, the mixture was stirred at 80° C. for 4 hours, and the reaction was terminated when it was confirmed by IR (infrared absorption) analysis of the reaction product that the isocyanate group had disappeared, thereby obtaining an isocyanuric ring-containing urethane (meth)acrylate compound (not corresponding to the acrylic modified isocyanurate (I) of the present invention).

[0052] Example 1 65 parts by weight of the acrylic modified isocyanurate (I) prepared in Synthesis Example 1, 35 parts by weight of Aronix M-313 (manufactured by Toa Gosei), 4 parts by weight of OMNIRAD 184D as a photopolymerization initiator, and 240 parts by weight of propylene glycol monomethyl ether as a solvent were weighed out and stirred in a container to prepare a hard coat solution 1 with a solid content concentration of about 30%. The hard coat solution 1 was applied to a PET film (125 μm / Toray U-34) using a bar coater #9, and then dried in an oven at 80° C. for 1 minute, and then irradiated with 350 mJ using an ultraviolet irradiator (manufactured by Eye Graphics / high pressure mercury lamp) to obtain a hard coat film with a film thickness of 5 μm. Table 1 shows the composition ratio of the resin, the film thickness of the PET film (substrate), the film thickness of the obtained hard coat film, etc. In addition, the product name "Aronix" is omitted from M-313 in the table, but the chemical formulas of the compounds contained in M-313 used are listed below.

[0053] Chemical formula of M-313 [ka] (In the above formula, R represents a hydroxyl group or -OCO-CH=CH2.) M-313 is supplied as a mixture containing 30-40% compounds where R is hydroxyl and 60-70% compounds where R is -OCO-CH=CH2.

[0054] The types of unsaturated compounds (II) used in other examples and comparative examples are exemplified below. Chemical formula of M-315 [ka] (In the above formula, R represents a hydroxyl group or -OCO-CH=CH2.) M-315 is supplied as a mixture containing 3-13% compounds where R is hydroxyl and 87-97% compounds where R is -OCO-CH=CH2.

[0055] Chemical formula of M-402 [ka] (In the formula, R 1 represents a hydroxyl group or -OCO-CH=CH2.)

[0056] Chemical formula of M-305 [ka] (In the formula, R 2 represents a hydroxyl group or -OCO-CH=CH2.)

[0057] UN3320-HS Art Resin UN3320-HS (manufactured by Negami Industrial Co., Ltd.) UN3320-HA Art Resin UN3320-HA (manufactured by Negami Industrial Co., Ltd.) M-220 Aronix M-220 (manufactured by Toa Gosei) M-240 Aronix M-240 (manufactured by Toa Gosei) M-350 Aronix M-350 (manufactured by Toa Gosei) M-360 Aronix M-360 (manufactured by Toa Gosei) M-309 Aronix M-309 [ka]

[0058] The anti-fogging properties of the obtained hard coat film (3-second fogging evaluation), turbidity (Hz), total light transmittance (Tt), and refractive index and reflectance (R) of the outermost coating layer were measured by the methods described below, and are shown as initial properties in Table 3. These correspond to Hz1, Tt1, and R1.

[0059] Anti-fog rating (3-second anti-fog rating) Ion-exchanged water was added to a 10 cm high glass container with an opening of 5 mm diameter to a height of 5 cm, and the temperature was maintained at 60° C. while stirring at 100 rpm with a hot magnetic stirrer. The obtained film was covered with a lid so that the hard coat film surface was placed in the glass container, and 3 seconds after that, the presence or absence of fogging due to steam was observed and judged according to the following criteria. ○: No cloudiness at all. ○△: Very slight cloudiness is visible △: Slight cloudiness is visible. △×: Cloudiness is visible ×: Clearly cloudy.

[0060] Turbidity (Hz) and total light transmittance (Tt) measurements For the measurements, Nippon Denshoku Industries Co., Ltd.'s NDH4000 was used, and the light source and method were set to D65 and JIS. The hard coat film surface was placed on the receiver side, and the total light transmittance and parallel light transmittance were measured. Diffuse light transmittance = Total light transmittance (Tt) - Parallel light transmittance Turbidity (Hz) = Diffuse Light Transmittance / Total Light Transmittance It is calculated as follows.

[0061] Refractive index The refractive index was measured at 589 nm D line using an Atago DR-M2 refractometer. The test film was placed on the prism surface, and 1-bromonaphthalene was used as the intermediate liquid.

[0062] Reflectance evaluation (Preparation for measurement) Black ink made by Teikoku Ink Co., Ltd. is applied to the side opposite the hard coat film of the evaluation sample using a bar coater and dried at 80° C. for 30 minutes to provide a 15 μm black printed layer. (Reflectance measurement) The reflectance was measured from the hard coat film side of the evaluation sample by the SCI method. The measurement was performed using SD7000 manufactured by Nippon Denshoku Industries Co., Ltd., with the measurement wavelength region being 380 nm or more and 780 nm or less, and the value at 550 nm was taken as the reflectance.

[0063] For the hard coat film obtained in Example 1, durability tests were conducted using 6% hypochlorous acid, 3% aqueous hydrogen peroxide solution, 70% ethanol solution, and 70% IPA, and then the above-mentioned 3-second haze evaluation, turbidity, total light transmittance, scratch resistance, and reflectance were measured, and the results are shown in Table 3. The durability tests were conducted as follows.

[0064] Durability evaluation (Preparing disinfectant) 6% hypochlorous acid solution (commercially available), 3% hydrogen peroxide solution (commercial product / oxydol), 70% ethanol solution (ethanol diluted with ion-exchanged water to a concentration of 70%) 70% IPA solution (Isopropanol (IPA) diluted with ion-exchanged water to a concentration of 70%) (Rubbing tester) Daiei Scientific Precision Machinery Co., Ltd., flat surface abrasion tester PA-300A (Rubbing test) Bencotton was placed on the terminal of the abrasion tester so that it was 2 cm square, and 4 ml of disinfectant was soaked into it. The abrasion test was carried out at a speed of 15 cm / sec. The load was 200 g, and the load per unit area was 50 g. The Bencotton was replaced every 20 strokes of the abrasion test, 4 ml of disinfectant was added again, and the abrasion test was then repeated. A total of 100 strokes of the abrasion test were performed in this procedure.

[0065] (Post-exam evaluation) Scratch resistance: After the test, scratches on the sample were evaluated on a 5-point scale according to the rating scale shown in FIG. In addition, the antifogging property, reflectance, total light transmittance and turbidity after the rubbing test were measured by the above-mentioned procedures and obtained as Hz2, Tt2 and R2. The differences from the initial properties were calculated and shown in Table 3.

[0066] Examples 2 to 9 A hard coat film was obtained in the same manner as in Example 1, except that the acrylic modified isocyanurate (I) and the unsaturated compound (II) shown in Table 1 were used. Thereafter, the above-mentioned evaluations were performed in the same manner as in Example 1, and the results are shown in Table 3.

[0067] Example 10 1.80 parts by weight of the acrylic modified isocyanurate (I) prepared in Synthesis Example 1, 0.45 parts by weight of Aronix M-313 (manufactured by Toa Gosei), 0.10 parts by weight of OMNIRAD 184D as a photopolymerization initiator, 13.75 parts by weight of Suluria 4320 (manufactured by JGC Catalysts and Chemicals / solid content concentration 20%) as a refractive index adjuster, and 154 parts by weight of propylene glycol monomethyl ether as a solvent were weighed and stirred in a container to prepare a low-refractive hard coat solution 13 with a solid content concentration of about 3%. The composition of the low-refractive hard coat solution 13 is shown in the column of the second layer of Example 13 in Table 1. Table 1 also shows the refractive index adjuster and the film thickness of the second layer.

[0068] The hard coat solution 4 of Example 1 was applied to a PET film (125 μm / Toray U-34) using a bar coater #9, and then dried in an oven at 80° C. for 1 minute. Then, the film was irradiated with 200 mJ of ultraviolet light using an ultraviolet irradiator (I-Graphics / high pressure mercury lamp) to obtain a hard coat film 4 having a thickness of 5 μm.

[0069] A low-refractive hard coat solution 13 was applied onto the hard coat film 4 using a bar coater #4, and then dried in an oven at 80°C for 1 minute. Thereafter, the solution was irradiated with 350 mJ of ultraviolet light using an ultraviolet irradiator (manufactured by Eye Graphics / high-pressure mercury lamp) to obtain a hard coat film 13 in which a low-refractive layer having a thickness of 100 nm was laminated onto a hard coat film having a thickness of 5 μm.

[0070] The obtained hard coat film 13 having the low refractive index layer laminated thereon was evaluated in the same manner as in Example 1, and the results are shown in Table 3.

[0071] Examples 11 to 17 A hard coat film having a low refractive index layer laminated thereon was obtained in the same manner as in Example 10, with the contents shown in Table 1. Each evaluation was carried out in the same manner as in Example 1, and the results are shown in Table 3.

[0072] Comparative Examples 1 to 13 A hard coat film was formed in the same manner as in Example 1 using the composition of the first or second layer shown in Table 2. Each evaluation was carried out in the same manner as in Example 1, and the results are shown in Table 4.

[0073] In Comparative Examples 1 and 2, the amount of acrylic modified isocyanurate (I) used is outside the specified range, and the anti-fogging properties are insufficient. In Comparative Example 3, the amount of polyethylene glycol in the acrylic modified isocyanurate (I) used is insufficient (Synthesis Example 3), so the water absorption is low and the anti-fogging properties are insufficient. In Comparative Examples 4 to 8, an unsaturated compound other than the unsaturated compound (II) is used, and the anti-fogging properties are insufficient. In Comparative Examples 9 to 12, the acrylic modified isocyanurate (I) is not used, and the composition is not cured, so that the performance evaluation was not possible. In Comparative Example 13, a combination of a commonly used hard coat layer and an anti-fogging agent, which is not the transparent cured resin layer of the present invention, is used, and the initial properties are satisfactory, but the composition is not durable for continuous use.

[0074] [Table 1]

[0075] [Table 2]

[0076] [Table 3]

[0077] [Table 4]

Claims

1. A transparent laminated member in which a transparent resin substrate layer and a transparent cured resin layer are laminated, When the total light transmittance of the transparent laminated member is Tt1, the turbidity is Hz1, and the reflectance is R1, 90%<Tt1<98%, 0.01%≦Hz1<2.0%, and 0.5%≦R1<5.0% Satisfy the relationship between The present invention is characterized in that, when distilled water is poured into a glass container having an opening of 5 cm in diameter so that the height of the container surface from the water surface is 5 cm, the temperature is kept at 60° C., and the glass container is covered with a lid so that the cured resin layer side of the transparent laminate member is in contact with water vapor, no fogging occurs for 3 seconds; The transparent cured resin layer was wiped 100 times with cotton soaked in 6% hypochlorous acid solution under a load of 50 g per unit area. After this, the total light transmittance of the transparent laminate member was Tt2, the turbidity was Hz2, and the reflectance was R2. 0≦|Tt1−Tt2|<1, 0≦|Hz1-Hz2|<2, and 0≦|R1-R2|<0.5 The transparent laminate member satisfies the above relationship, and is characterized in that when distilled water is poured into a glass container having an opening of 5 cm in diameter so that the height of the container surface from the water surface is 5 cm, the temperature is kept at 60°C, and the glass container is covered with a lid so that the cured resin layer side of the transparent laminate member is exposed to water vapor, no fogging occurs for 3 seconds.

2. The transparent laminate member according to claim 1, wherein the relationship between the total light transmittance, turbidity and reflectance is the same even when the 6% hypochlorous acid solution is replaced with a 3% hydrogen peroxide solution, a 70% ethanol solution or an isopropyl alcohol solution.

3. The transparent cured resin layer is composed of two layers, the first layer laminated on the transparent resin substrate layer has a thickness of 2 to 10 μm and a refractive index of 1.48 to 1.54; 3. The transparent laminate member according to claim 1, wherein the second layer laminated on the first layer has a thickness of 70 to 130 nm and a refractive index of 1.36 to 1.

42.

4. 4. The transparent laminate member according to claim 1, wherein the transparent resin substrate is made of a polyester resin and has a thickness of 75 to 250 μm.

5. The transparent cured resin layer is formed of a compound having the chemical formula: 【Chemistry 1】 (In the chemical formula, n, m, and o independently represent integers, and n+m+o=12 to 24.) The transparent laminate member according to any one of claims 1 to 4, characterized in that it contains an acrylic-modified isocyanurate (I) having the formula:

6. 6. The transparent laminate member according to claim 5, wherein the acrylic modified isocyanurate (I) is contained in the resin forming the transparent cured resin layer in an amount of 65 to 95% by weight of the resin solid content.

7. 7. The transparent laminate member according to claim 5 or 6, wherein the cured resin layer contains an unsaturated compound (II) having either a hydroxyl group or an unsaturated double bond group and an unsaturated double bond group having two or more functionalities in an amount of 5 to 35% by weight based on the weight of the resin component; The unsaturated compound (II) has the following chemical formula: 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the chemical formula, R, R 1 and R 2 are independently a hydroxyl group or -OCO-CH=CH 2 Represents.) A transparent laminate member comprising any one of the following:

8. The transparent laminate member according to claim 3, characterized in that the cured resin layer constituting the second layer contains hollow silica having an average particle size of 35 to 70 nm in an amount of 35 to 65 wt % in terms of solid content weight.

9. A face shield using the transparent laminate member according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Fixing and supporting ring in shield construction method

    JP1984085100A

  • Coating agent composition, coating product prepared by curing the same, and antifogging sheet

    JP2005330439A

  • Curable composition, highly heat-resistant transparent resin, and optical component

    JP2006249220A

  • Coating composition having Anti-reflective and Anti-fogging properties

    JP2010106282A

  • Antifogging antireflection film

    JP2019142196A